2018
DOI: 10.1016/j.apsb.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

3D tissue engineering, an emerging technique for pharmaceutical research

Abstract: Tissue engineering and the tissue engineering model have shown promise in improving methods of drug delivery, drug action, and drug discovery in pharmaceutical research for the attenuation of the central nervous system inflammatory response. Such inflammation contributes to the lack of regenerative ability of neural cells, as well as the temporary and permanent loss of function associated with neurodegenerative diseases such as Alzheimer's disease, Parkinson's disease, and traumatic brain injury. This review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 119 publications
(181 reference statements)
0
43
0
Order By: Relevance
“…Our 3D human cell culture model is vital for studying many human CNS diseases, which is inaccessible in 2D cultures 26 . To improve the use of 3D scaffolds for drug screening and drug delivery purposes, it is required to alter the chemical and biophysical properties of the materials to better suit of the needs of the cultured cells and native tissues 27 . Taking traumatic brain injury (TBI) as an instance, we showed that human cortical neurons responded to physiologically relevant impact forces.…”
Section: Discussionmentioning
confidence: 99%
“…Our 3D human cell culture model is vital for studying many human CNS diseases, which is inaccessible in 2D cultures 26 . To improve the use of 3D scaffolds for drug screening and drug delivery purposes, it is required to alter the chemical and biophysical properties of the materials to better suit of the needs of the cultured cells and native tissues 27 . Taking traumatic brain injury (TBI) as an instance, we showed that human cortical neurons responded to physiologically relevant impact forces.…”
Section: Discussionmentioning
confidence: 99%
“…Additional functional groups such as targeting ligands 48 , enzyme-responsive groups49, 50, 51, drugs52, 53, fatty acids54, 55, DNA 56 , chelator 57 , fluorophores 58 can be integrated into peptide gelators without disturbing their capability in hydrogel formation. These peptide-based hydrogels have found broad biomedical applications in areas, such as tissue engineering 59 , drug delivery 60 and imaging58, 61.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, by using biocompatible materials in the form of three-dimensional (3D) scaffolds for cell growth and differentiation, it is possible to obtain in vitro biological constructs that resemble, in terms of morphology and function, the native tissues more closely than conventional bi-dimensional (2D) cell cultures [14]. As a consequence, 3D tissue-engineered constructs represent valuable models to assess the effect of new drugs in a more reliable manner [15]. A number of biomaterials and technologies have been used to create TE scaffolds.…”
Section: Introductionmentioning
confidence: 99%